Study of Population and Damage Intensity by Necrobia rufipes Pest on Copra - Patty, John A; Masauna, Esther D; Ponira, Ponira (Universitas Pattimura, 2023)
The problem of copra damage in storage warehouses by the warehouse pest Nercrobia rufipes is a serious matter because it can reach >10%, is not easy to overcome and causes significant losses. The aim of the study was to obtain the total population of N. rufipes (eggs, larvae, pupae and imago) and the intensity of damage in three storage warehouses in Ambon City. This research was carried out using a survey method at Alam Mas Bersatu, Widya Abadi and UD Sepakat warehouses, from April to June 2018. Samples were taken from several piles blocks and 500 grams of copra sample were taken from each pile from each stratum (upper, middle and lower stratum). The parameters observed were damage symptoms, damage intensity and total population of N. rufipes pest. The results showed that the highest intensity of N. rufipes pest damage was found in the Alam Mas Bersatu warehouse (35.92%) and was classified as moderate damage, followed by those those at UD Sepakat warehouse (21.43%) and Wadya Abadi (7.42%), both classified as light damage. The highest population of N. rufipes was found at the Alam Mas Bersatu warehouse, i.e. larva population (35.29 individuals), pupae (2.33 individuals), imago (6.43 individuals). At UD Sepakat warehouse, the population consisted of larvae (28.83 individuals), pupae (3.83 individuals) and imago (6.33 individuals). The lowest population was at Widya Abadi warehouse, consisted of larvae (5.83 individuals), pupae (0 or not found) and imago (0.5 individuals).